Do Beliefs and Behaviors relate to Dental / oral Health, Body Appreciation, and Quality of life Differ Among Adults in Arab Societies? - Basha, Shaimaa Ezzat; Badawy, Sherine; Kalluvalappil, Nabeel Ayappali; Harhash, Asmaa (Dirasat: Human and Social Sciences, 2026)
Objectives: This study aims to assess and compare beliefs and behaviors related to oral health, body image perception, and quality of life among adults in Arab communities, specifically focusing on Emirati, Saudi, and Egyptian populations. Methods: The sample included 934 participants (mean age: 21.85 years) divided into three groups: Emiratis (12.2%), Saudis (26.2%), and Egyptians (61.6%). Participants completed three validated scales: the Body Appreciation Scale-2 (BAS-2), the Dental Oral Health Beliefs Scale (DOHBS), and the abbreviated version of the World Health Organization Quality of Life Scale (WHOQOL-BREF). Results: The findings revealed significant differences among the groups in oral health beliefs, body image perception, and quality of life. Emirati participants scored significantly higher than Saudis and Egyptians in health-related variables, with moderate differences of 1.545 (p = 0.016) and 1.797 (p = 0.001), respectively. Additionally, positive correlations were observed between body image appreciation and quality of life scores, while an inverse relationship was noted between positive general health perceptions and quality of life evaluations. Gender and cultural factors were also found to have a significant impact on health perceptions. Conclusion The study highlights substantial variations in health-related beliefs and behaviors across Arab communities. Emirati participants demonstrated better health outcomes compared to their Saudi and Egyptian counterparts, emphasizing the role of cultural and demographic factors. The findings underscore the need for culturally tailored health interventions to enhance oral health, body image perception, and quality of life across different communities.